Strategies for promoting learners’ motivations by the medium of teachers in English as a second language: A pilot approach in Benin secondary schools - Azoua Mathias Hounnou; Bienvenu Adjoha; Coffi Martinien Zounhin-Toboula (Eureka: Journal of Educational Research, 2024)
Motivation takes a core position in a language classroom. It drives students’ interest and attention to the learning process. Motivated learners are willing to take action and feel responsible for what they learn. The present study conducted in “LMB” secondary school (North Benin) has aimed to analyze qualitatively the motivational strategies applied by teachers in ESL/L2 teaching and learning contexts. The sample surveyed consisted of ten English teachers and ten pedagogical groups of first-year learners. A qualitative approach through interviews and questionnaires was used. Discourse analysis was deployed as an information processing technique. The findings have revealed that teachers motivate learners at three levels: creating the basic motivational conditions, generating initial motivation, and maintaining and protecting motivation. It was demonstrated that a teacher’s self-brand and his attitudes toward learners are very important for motivating learners in classes. In addition, teachers utilize various strategies to enhance learners' awareness of the utility of the English language for their future. This study calls on the teachers’ responsibility to increase learners’ motivation.